Managing Electoral Logistics under Uncertainty: Risk, Coordination, and Institutional Learning in Indonesia’s 2024 Simultaneous Election - Samsudin; Suryawahyuni Latief; Suparmin; Wu hui Hua (Bulletin of Community Engagement, 2026)
Electoral logistics represent one of the most risk-prone components of election administration, particularly in large and decentralized democracies. This study aims to examine how electoral logistics were managed under conditions of uncertainty in Indonesia’s 2024 Simultaneous Election, with a specific focus on risk management, coordination, and institutional learning. The research employs a descriptive qualitative approach using a case study in Jambi City. Data were collected through semi-structured interviews with election officials and stakeholders, field observations of logistics distribution, and analysis of electoral regulations and official documents. The findings indicate that although logistics management formally complied with national regulations, risk anticipation remained limited, coordination mechanisms were largely reactive, and institutional learning was weak. Logistical disruptions were addressed through ad hoc solutions rather than systematic risk mitigation strategies. This study concludes that strengthening electoral logistics requires a shift from procedural compliance toward adaptive risk governance and structured learning mechanisms to enhance electoral integrity and administrative resilience.